2020
DOI: 10.1038/s41598-020-72536-z
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological study of native medicinal plants and the impact of pastoralism on their loss in arid to semiarid ecosystems of southeastern Iran

Abstract: The purpose of this study was to gather ethnopharmacological information on plants used by the pastorals of southeastern Iran. The relationships between ecological value of the plant species and ethnobotanical indices were investigated. The loss of medicinal plants and its effective factors were also determined under nomadism and sedentary pastoralism. Ethnopharmacological information of plants was collected through interviews with 85 local people including nomads (43%) and sedentary pastorals (57%). Ethnobota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
(47 reference statements)
3
3
0
Order By: Relevance
“…Significantly, no negative association between the indices was found. In order to determine the linear relationship between the ethnobotanical indices, Sharafatmandrad and Mashizi [ 75 ] and Cao et al [ 76 ] applied the correlation test; furthermore, their results were somewhat consistent with those of the present study.
Fig.
…”
Section: Resultssupporting
confidence: 87%
“…Significantly, no negative association between the indices was found. In order to determine the linear relationship between the ethnobotanical indices, Sharafatmandrad and Mashizi [ 75 ] and Cao et al [ 76 ] applied the correlation test; furthermore, their results were somewhat consistent with those of the present study.
Fig.
…”
Section: Resultssupporting
confidence: 87%
“…This group of interviewees was more knowledgeable about plants and their utilization and shared most of the documented information. Other ethnobotanists have reported similar results (Bendif et al 2018, Sharafatmandrad & Khosravi Mashizi 2020.…”
Section: Discussionsupporting
confidence: 67%
“…Men usually manage the fieldwork, while women were often involved in domestic activities, which were sometimes associated with the use of plant species or their products to keep the family healthy. Some recent ethnobotanical studies have also reported richer female knowledge of plant uses (Mohamadi et al 2015, Mosaddegh et al 2012, Sharafatmandrad & Khosravi Mashizi 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The species that were locally protected, and often less available, were found to be associated with the greatest ethnomedicinal knowledge. A similar tendency has been shown elsewhere (Sharafatmandrad and Khosravi Mashizi, 2020). The harvesting of species with high popularity levels, and thus associated with high knowledge levels, may lead to sustainability problems (Posthouwer et al, 2016).…”
Section: Ecological Parameters Driving Vegetation Shape Through Ethno...supporting
confidence: 73%